Inji Efflatoun and the Mexican Muralists- Imaging Women and Work between Egypt and Mexico - Gabriella Nugent; Inji Efflatoun; Sharjah Art Foundation (Sharjah Art Foundation, 2022)
Inji Efflatoun and the Mexican Muralists: Imaging Women and Work between Egypt and Mexico traces Efflatoun s relationship with key figures in the Mexican mural movement, and was produced as part of Sharjah Art Foundation s annual Publishing Grant in 2020. The essay traces Efflatoun s relationship with key figures in the Mexican mural movement, including David Alfaro Siqueiros, Diego Rivera and José Clemente Orozco, and explores the ways in which she challenged the masculinist assumptions of artistic modernism.
SAF Publishing Grant 2020.
English
Keywords: N4390-5098 Visual Arts- Exhibitions